HUBUNGAN POLA ASUH IBU DENGAN PERILAKU SULIT MAKAN PADA ANAK USIA PRASEKOLAH DI PERUMNAS II KELURAHAN BENCONGAN - Merdi Mesio Nardi Leosae (Nusantara Hasana Berdikari, 2021)
One of the factors that can cause lack of nutritional intake in children is eating difficult behavior. This study aims to determine whether there is a relationship between mother's upbringing and eating difficult behavior in preschool children in Perumnas II, Bencongan, Tangerang, Banten. This research design is descriptive correlational with cross sectional approach. The sampling method is non-probability sampling with incidental sampling technique. The number of samples was as many as 70 mothers in Perumnas II, Bencongan Village. Based on the results of the data analysis of the relationship between maternal parenting and eating difficult behavior in preschool children in Perumnas II, Bencongan Village, it was found that: 1) A total of 54 mothers (77.1%) applied good parenting patterns and those who applied bad parenting patterns were 16 mother (22.9%); 2) 22 children (31.4%) experienced difficulty eating behavior and those who did not experience difficulty eating, as many as 48 children (68.6%); 3) Value of Asymp.Sig. (2-sided) in the Chi-Square test is 0.002 or less than 0.05. The conclusion of this study is that there is a relationship between maternal parenting and eating difficult behavior in children aged 5-6 years in Perumnas II, Bencongan Village, Tangerang Regency. It is recommended to mothers in Perumnas II of Bencongan Village to change their children's eating patterns by implementing parenting with good categories, namely democratic or authoritarian parenting.